Pengaruh Struktur Modal, Kinerja Keuangan Terhadap Mva Pada Perusahan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bei - Eva Widiarti; Arisyahidin Arisyahidin (Universitas Islam Kadiri, 2020)
This study aims to analyze the effect of leverage, liquidity, and profitability on market value added. There are 25 companies manufacturing consumer goods industry sectors listed on the IDX that were used as samples during the 2016-2018 period. Sampling technique used in this research is purposive sampling. Furthermore, statistical tests are used in data analysis and Hypothesis testing is multiple linear regression. The independent variable consists of DER (dedt to equity ratio), CR (Current Ratio) and ROA (Return on assets). While the dependent variable used is market value added (MVA). The results show that only returns assets (ROA) have a significant and positive impact on market value added (MVA). Meanwhile, leverage ratio (DER) and liability ratio (CR) do not show a significant effect on MVA.